Effectiveness of Electronic Muhammadiyah Monitoring Chronic Disease Application in Changing The Knowledge, Attitudes, and Behavior of People With Hypertension - Ni Putu Susari Widianingsih; Mahendro Prasetyo Kusumo (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Hypertension (HT) is a serious medical condition that significantly increases the risk of heart, brain, kidney, and other organ diseases. The disease course increases along with age and a bad lifestyle. One strategy to prevent the increasing number of HT sufferers is through health promotion. In the digital era, technology is a strategic approach to controlling HT. One of Indonesia's existing health applications is the Electronic-Muhammadiyah Monitoring Chronic Disease (E-MMCD) application. However, its effectiveness has not been tested in increasing the knowledge, attitudes, and behavior of people with HT. This quasi/experimental research was conducted using consecutive purposive sampling at Husada Utama Hospital, Surabaya, from September to November 2022. The number of samples was 57 patient respondents for each group, the intervention (I) and the control (C) group. The data was carried out using the pre-and post-test questionnaire after 1 month intervention period using the E-MMCD application. In group C, health promotion using applications was not given. Knowledge in groups C and I was insignificant different. Attitudes and behavior in group C were increased with an insignificant difference, while in group I were increased with a significant difference.